The Effect of On Time Performace on Ticket Buying Interest by Garuda Indonesia Airline Consumers at Komodo Airport - Kurniasari, Zenita; Amarda, Regy Tofanni (Journal Of Accounting Management Business And International Research, 2022)
Rivalry between airline companies makes airlines compete to provide the best service for every customer. One of the factors to increase buying interest is timeliness or On Time Performance (OTP). OTP is a consideration for consumers in choosing an airline. This study aims to determine how much influence On Time Performance (OTP) has on the interest in buying Garuda Indonesia airline tickets at Komodo Airport. The method used in this study is a quantitative method. The data sources in this study are Garuda Indonesia airline consumers who pass through Komodo Labuan Bajo Airport in the period from June 2021 to December 2021. The data collection technique in this study uses a questionnaire technique distributed online. The number of respondents in this study were 100 respondents. The results of the study indicate that the On Time Performance (OTP) variable partially has a significant influence on the Consumer Ticket Purchase Interest of Garuda Indonesia Airlines at Komodo Airport Labuan Bajo in the period June 2021 to December 2021. The effect of On Time Performance (OTP) on buying interest Garuda Indonesia airline tickets at Komodo Airport amounted to 38.3% and the remaining 62.7% was explained by other variables not discussed in this study such as ticket prices, services, route availability, aircraft types and others.